Irregularities in Consumer Credit Agreements in Poland, the Contex of Consumer Protection in the Financial Services Market - Czechowska, Iwona Dorota; Hajdys, Dagmara; Ślebocka, Magdalena (Journal of Finance and Financial Law, 2023)
The purpose of the article and the research question. The aim of the article is to present and evaluate the functioning of the banking market in Poland from the perspective of the safety of banking services related to consumer protection. The realisation of the objective was limited to consumer credit market and the irregularities identified by consumer protection institutions during the COVID-19 pandemic. The article poses the research questions: What measures have been taken by the government and the banking sector to protect consumers from the consequences of the COVID-19 pandemic? Which institutions are part of the system of consumer protection on the banking services market? What irregularities were reported by borrowers in the banking sector? Methodology. The research focused on the literature review, regulations introduced in relation to the COVID-19 pandemic and data on rulings issued by the Banking Ombudsman and the Office of Competition and Consumer Protection related to banking market failures against consumers. Results of the research. It has been found that “Credit holidays” were a way of protecting the financial situation of consumers/borrowers during the COVID-19 pandemic, when they lost their jobs or their source of income. Customers reported irregularities to: Financial Ombudsman, Office of Competition and Consumer Protection and Bank Arbitrator. The large number of credit offers, their high level of complexity and the low impact on the credit agreement meant that the consumer was exposed to unfair and unethical practices of creditors. Irregularities occurred both at the pre-contractual stage and during and after the credit agreement.